1993
DOI: 10.1212/wnl.43.9.1828
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography and histopathology in Creutzfeldt‐Jakob disease

Abstract: We studied a 62-year-old man with Creutzfeldt-Jakob disease (CJD), using positron emission tomography (PET) and (18F)-2-fluoro-2-deoxy-D-glucose (FDG). Glucose metabolism was heterogeneously decreased throughout the brain. At autopsy, regional distributions of spongiosis, astrogliosis, and neuronal loss correlated with premortem regional metabolic deficits. These results suggest that PET with FDG may provide metabolic regional markers for CJD neuropathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Asymmetry in the distribution of the hypometabolic regions has been found, and frontal, parietal and temporal reduction in glucose uptake has been described [24,25,26]. However, in order to perform the PET examinations, anaesthesia was necessary in these severely demented patients, which raised the question of the effects of propofol administration on rCMR glu and DED binding.…”
Section: The Effect Of Anaesthesiamentioning
confidence: 99%
“…Asymmetry in the distribution of the hypometabolic regions has been found, and frontal, parietal and temporal reduction in glucose uptake has been described [24,25,26]. However, in order to perform the PET examinations, anaesthesia was necessary in these severely demented patients, which raised the question of the effects of propofol administration on rCMR glu and DED binding.…”
Section: The Effect Of Anaesthesiamentioning
confidence: 99%
“…In CJD disseminated areas of hypometabolism (PET) [12,16,18,23,45] or hypoperfusion (SPECT) [1,8,11,18,21,26,27,32,36,44,47] of cortical and subcortical structures in CJD were described in single case reports or few cases. The aim of this study was to explore whether typical sites or even patterns of regional metabolic changes could be found in a larger sample of CJDcases and to evaluate possible correlations between PET findings, MRI and the clinical symptomatology.…”
Section: Introductionmentioning
confidence: 99%
“…Disruption of the CPC tract may have contributed to cerebellar-like ataxia in our patient. Previous studies of CJD patients have reported that MRI or FDG PET, neuropathological, and clinical findings closely correlate [9][10][11][12]. Disruption of cerebro-cerebellar loops, resulting in crossed cerebellar diaschisis, is a novel finding that may provide a clue to the mechanism underlying ataxic hemiparesis in CJD.…”
mentioning
confidence: 85%